Corrosion-resistant, non-stick coatings and layers, methods for their production and use
Patent Information
- Application Number
- CN202410982532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-22
AI Technical Summary
Existing technologies cannot effectively solve the problem of coal powder sticking and clogging in coal silos, especially when the inner wall of the coal silo is uneven or corroded. This results in high sliding resistance of coal powder, which easily forms coal arches and affects the stability of industrial production.
By adding anti-adhesion filler components such as hydrophobically modified micro/nano silica particles and micron-sized silicon carbide particles to the coating, combined with organosilane crosslinking reaction, a coating with low surface energy and acid corrosion resistance is prepared, thereby improving the anti-adhesion and long service life performance of the coating.
The prepared coating has a high contact angle and strong bonding strength, which can effectively prevent the coal powder feeding silo from sticking and arching, extend the service life to more than two years, and is suitable for large, medium and small coal powder feeding silos, thus reducing costs.
Smart Images

Figure CN118791970B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coatings technology, specifically to a corrosion-resistant and anti-adhesion coating and coating layer, its preparation method, and its application. Background Technology
[0002] Many industrial processes in my country rely on coal for heat. Coal pulverizer silos, serving as both storage and conveying devices, frequently experience clogging and arching issues, significantly impacting the stability of industrial production. Besides factors such as the silo's structure, the moisture content of the coal pulverizer, and storage time, the adhesion and arching of coal pulverizer within the silo are directly related to the surface condition of the silo's inner walls. Welding repairs, pressure deformation, and corrosion create uneven surfaces on the silo's inner walls, providing a place for coal pulverizer to accumulate. This also increases the friction coefficient of the silo walls. Greater friction between the coal pulverizer and the silo walls leads to greater sliding resistance, making it easier for coal arching to form and ultimately causing clogging.
[0003] Currently, measures to address the issues of coal powder silo adhesion and clogging include manual tapping of the silo's outer wall, air jet impact, and internal wear-resistant liners. However, manual tapping is time-consuming, labor-intensive, and inefficient; air jet impact requires a large initial investment and is costly; and internal wear-resistant liners are expensive and only suitable for large silos. Therefore, existing technologies are not yet perfect for solving the problem of coal powder silo adhesion and clogging. Developing a low-cost, long-life, and widely applicable anti-adhesion and clogging technology is a pressing issue for technical personnel. Summary of the Invention
[0004] Due to the aforementioned deficiencies in existing technologies, this invention provides a corrosion-resistant and anti-adhesion coating and its preparation method, as well as its application in pulverized coal feeding silos. The coating, by adding anti-adhesion filler components, constructing a low surface energy coating surface, and enhancing acid corrosion resistance, exhibits excellent anti-adhesion and silo clogging characteristics, as well as corrosion resistance and a long service life.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] In a first aspect, the present invention provides a method for preparing a corrosion-resistant and anti-adhesion coating, characterized by comprising the following steps:
[0007] 12 parts of methyltriethoxysilane and 6 parts of dimethyldiethoxysilane were ultrasonically dispersed in a mixed solution of 120 parts of isopropanol and water. The pH of the solution was adjusted to 4-5. 10 parts of polytetrafluoroethylene powder were added, and the mixture was stirred and reacted completely at 70-80°C. Then, 6-14 parts of hydrophobically modified micro / nano silica particles and 3-6 parts of micron silicon carbide particles were added, and the mixture was stirred and reacted completely at 50-60°C to prepare a corrosion-resistant and anti-adhesion coating.
[0008] The preparation method utilizes the activity of silanol groups after hydrolysis of organosilanes to encapsulate hydrophobically modified micro / nano silica particles, micron-sized silicon carbide particles, and polytetrafluoroethylene powder into organosilicon polymers, thereby causing cross-linking between organosilanes to form a coating with good curing effect and high density.
[0009] Furthermore, the isopropanol and water mixture has a ratio of M(isopropanol):M(water) of 5:2; and the pH of the solution is adjusted to pH 4.5 using acetic acid.
[0010] Furthermore, the amount of the hydrophobically modified micro / nano silica particles used is 10-14 parts.
[0011] Further, the preparation method of the hydrophobic modified micro / nano silica particles is as follows: 90 parts of anhydrous ethanol, 10 parts of purified water and 4 parts of ammonia water are placed in a three-necked flask and stirred evenly at 50-60°C. Then, 10 parts of tetraethyl silicate are added dropwise and stirred continuously to obtain a uniform mixed emulsion. 2-5 parts of silica micropowder are added to the mixed emulsion and stirred evenly. Then, 2 parts of hexadecyltrimethoxysilane are added dropwise and stirred continuously until the reaction is complete. After centrifugation and washing with anhydrous ethanol, the mixture is placed in a drying oven and dried completely to obtain hydrophobic modified micro / nano silica particles.
[0012] Due to the high hydroxyl content and surface energy of silica, it is prone to agglomeration and difficult to disperse uniformly. Modification with hexadecyltrimethoxysilane can effectively reduce its surface energy. The modification of micro / nano silica particles with hexadecyltrimethoxysilane mainly involves the condensation reaction between the silanol groups (R-Si(-OH)3) produced by the hydrolysis of the active methoxy groups in hexadecyltrimethoxysilane and the hydroxyl groups (Si-OH) on the surface of micro / nano silica under alkaline conditions in an alcohol-water solvent. This introduces a large number of hydrophobic alkyl long chains, preparing modified micro / nano silica and improving its dispersibility and hydrophobicity in the organic phase system of coating slurries.
[0013] Secondly, the present invention provides a corrosion-resistant and anti-adhesion coating, characterized in that the corrosion-resistant and anti-adhesion coating is prepared by the preparation method described above.
[0014] Thirdly, the present invention provides a corrosion-resistant and anti-adhesion coating, characterized in that the corrosion-resistant and anti-adhesion coating prepared by the above preparation method is sprayed onto a substrate and naturally air-dried to form the coating.
[0015] Furthermore, the coating is composed of organosilanes, polytetrafluoroethylene, hydrophobically modified micro / nano silica, and silicon carbide.
[0016] Furthermore, the coating has a thickness of 60–100 micrometers, a contact angle of 140° or more, and a bonding strength with the substrate of 28 MPa or more.
[0017] Finally, the present invention provides an application of a corrosion-resistant and anti-adhesion coating or coating on the wall panel of a pulverized coal feeding silo.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) Compared with existing preparation methods, the coating preparation method of the present invention has fewer preparation steps, and the materials are readily available and inexpensive; the coatings prepared based on crosslinking and condensation reactions have uniform texture and the spraying quality is easy to guarantee.
[0020] (2) The coating of this invention incorporates polytetrafluoroethylene and hydrophobically modified micro / nano silica as anti-adhesion filler components, silicon carbide as a toughening component, and organosilane as a matrix, resulting in a water contact angle of over 140° and a bonding strength with the matrix of over 28 MPa. It exhibits slow corrosion in strong acids and possesses high bonding strength and excellent acid corrosion resistance and anti-adhesion properties. Currently, coatings with similar functions in practical applications generally have a lifespan of less than six months, while the coating of this invention has a lifespan of over two years.
[0021] (3) The coatings and coatings of the present invention are applicable to various pulverized coal feeding silos of all sizes, and have a good effect on solving the problems of adhesion, bridging and acid corrosion in pulverized coal feeding silos. Attached Figure Description
[0022] The invention, its features, and advantages will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings. Like reference numerals denote like parts throughout the drawings. The drawings are not drawn to scale; their purpose is to illustrate the gist of the invention.
[0023] Figure 1 This is a schematic diagram of the preparation process of a corrosion-resistant and anti-adhesion coating in one embodiment of the present invention.
[0024] Figure 2 The image shows the acid corrosion resistance weight loss diagrams of the coatings of samples 1#, 2#, 3#, 4#, 5#, 6#, and 7# in one embodiment of the present invention. The image also includes wetting angle test diagrams of samples 1#, 2#, 3#, and 7#. Detailed Implementation
[0025] The structure of the present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.
[0026] The reaction apparatus, compounds, and solvents involved in the following examples and illustrations are all commercially available.
[0027] The testing instruments and reagents used in the following examples are all commercially available, and the testing methods employed are existing technologies that can be found online. The sulfuric acid corrosion test was designed according to GB / T 28907-2012 standard, with a corrosion temperature of 30℃, a sulfuric acid concentration of 20%, and a total immersion time of 24 hours. The weight loss data of each sample before and after the corrosion test were recorded.
[0028] Contact angle (or wetting angle) testers are commercially available. Place the sample on the tester's platform, drop a 5μL water droplet onto the surface, and take a picture to obtain the contact angle between the water droplet and the coating surface.
[0029] Matters not covered in the description of this invention are common knowledge.
[0030] This invention first provides a method for preparing a corrosion-resistant and anti-adhesion coating, comprising the following steps:
[0031] 12 parts of methyltriethoxysilane and 6 parts of dimethyldiethoxysilane were ultrasonically dispersed in a mixed solution of 120 parts of isopropanol and water. The pH of the solution was adjusted to 4-5. 10 parts of polytetrafluoroethylene powder were added, and the mixture was stirred and reacted completely at 70-80°C. Then, 6-14 parts of hydrophobically modified micro / nano silica particles and 3-6 parts of micron silicon carbide particles were added, and the mixture was stirred and reacted completely at 50-60°C to prepare a corrosion-resistant and anti-adhesion coating.
[0032] As a preferred technical solution, further: the mass ratio of isopropanol to water in the isopropanol and water mixture is 5:2, which mainly acts as a diluent and provides a reaction environment in the reaction system.
[0033] As a preferred technical solution, further: the pH of the solution is adjusted to pH=4.5 using acetic acid. In an acidic alcohol-water solvent, methyltriethoxysilane and dimethyldiethoxysilane hydrolyze to form a large amount of Si-OH. In a medium-temperature alcohol-water solvent, the Si-OH bonds condense with the Si-OH bonds on the modified silica, thereby forming a polymer coating material.
[0034] During the formation of the polymer coating material, methyltriethoxysilane interacts with the Si-OH generated by the hydrolysis of dimethyldiethoxysilane, which encapsulates and aggregates the modified silica particles, forming a cross-linked network structure dominated by Si-O-Si, which greatly increases the strength and toughness of the coating material.
[0035] As a preferred technical solution, further: the preparation method of the hydrophobic modified micro / nano silica particles is as follows: take 90 parts of anhydrous ethanol, 10 parts of purified water and 4 parts of ammonia water into a three-necked flask, stir evenly at 50-60℃, then add 10 parts of tetraethyl silicate dropwise, and continue stirring to obtain a uniform mixed emulsion; take 2-5 parts of silica micro powder and add it to the mixed emulsion and stir evenly, then add 2 parts of hexadecyltrimethoxysilane dropwise, and continue stirring until the reaction is complete, then centrifuge and wash with anhydrous ethanol, and place in a drying oven to dry completely to obtain hydrophobic modified micro / nano silica particles.
[0036] Due to the high hydroxyl content and surface energy of silica, it is prone to agglomeration and difficult to disperse uniformly. Modification with hexadecyltrimethoxysilane can effectively reduce its surface energy. The modification of micro / nano silica particles with hexadecyltrimethoxysilane mainly involves the condensation reaction between the silanol groups (R-Si(-OH)3) produced by the hydrolysis of the active methoxy groups in hexadecyltrimethoxysilane and the hydroxyl groups (Si-OH) on the surface of micro / nano silica under alkaline conditions in an alcohol-water solvent. This introduces a large number of hydrophobic alkyl long chains, preparing modified micro / nano silica and improving its dispersibility and hydrophobicity in the organic phase system of coating slurries.
[0037] From the description of the preparation method above, it can be found that:
[0038] The preparation method provided by this invention utilizes the activity of silanol groups after hydrolysis of organosilicones to encapsulate hydrophobically modified micro / nano silica particles, micron-sized silicon carbide particles, and polytetrafluoroethylene powder into organosilicon polymers, thereby causing cross-linking between organosilicon molecules to form a coating with good curing effect and high density.
[0039] The present invention also provides a corrosion-resistant and anti-adhesion coating prepared by the above preparation method, a corrosion-resistant and anti-adhesion coating obtained by spraying the corrosion-resistant and anti-adhesion coating onto a substrate and allowing it to air dry naturally, and the application of the coating and coating in the wall panel of a pulverized coal feeding silo.
[0040] The technical solution and its effects of the present invention will be described in detail below with reference to specific embodiments.
[0041] Example 1
[0042] See Figure 1270g of anhydrous ethanol, 30g of purified water, and 12g of ammonia were placed in a three-necked flask and stirred at 50°C for 30 minutes. Then, 30g of tetraethyl silicate was added dropwise, and stirring was continued for 2 hours to obtain a mixed emulsion. 6g of silica micropowder was added to the mixed emulsion, and stirring was carried out for 1 hour. Then, 6g of hexadecyltrimethoxysilane was added dropwise, and the reaction was continued for 3 hours. After centrifugation for 30 minutes, the mixture was washed with anhydrous ethanol and dried in a drying oven at 70°C for 12 hours to obtain hydrophobically modified micro / nano silica particles.
[0043] 12g of methyltriethoxysilane and 6g of dimethyldiethoxysilane were ultrasonically dispersed in a mixture of 120g isopropanol and water, where the ratio of isopropanol to water was 5:2. The pH of the solution was adjusted to 4.5 with acetic acid, and 10g of polytetrafluoroethylene powder was added. The mixture was stirred and reacted at 70℃ for 6 hours. This process was repeated 7 times to prepare 7 samples. Then, 2, 4, 6, 8, 10, 12, 14g, and 16g of hydrophobically modified micro / nano silica particles and 3g of micron-sized silicon carbide particles were added to the 7 samples, respectively, and named samples 1#, 2#, 3#, 4#, 5#, 6#, 7#, and 8#. The system was stirred and reacted at 50℃ for 5 hours to prepare 8 corrosion-resistant and anti-adhesion coatings containing different mass fractions of hydrophobically modified micro / nano silica.
[0044] The prepared coating was sprayed onto the substrate and allowed to air dry naturally at 25°C for 48 hours, resulting in a coating thickness of 60 micrometers. This completed the preparation of a corrosion-resistant and anti-adhesion coating suitable for preventing sticking and clogging in coal powder silos. Experiments revealed that sample #8 exhibited cracking after drying. This was due to increased silica content, insufficient solvent dissolution of excessive filler particles, surface cracks after curing, and an inability to form a uniform film.
[0045] The acid resistance of seven coating samples from Example 1 was tested. The sulfuric acid corrosion test was designed according to GB / T28907-2012 standard, with a corrosion temperature of 30℃, a sulfuric acid concentration of 20%, and a full immersion time of 24 hours. The corrosion weight loss and water contact angle data for each sample after the test are as follows: Figure 2 As shown, the coating samples with a large contact angle (good hydrophobicity) exhibit strong acid corrosion resistance. Samples with 6–14 g of hydrophobically modified micro / nano silica added have a contact angle greater than 90° and a corrosion rate less than 0.6 mg / cm². 2 h) -1 Among them, the samples containing 10-14g of hydrophobically modified micro / nano silica exhibited better hydrophobic properties and a corrosion rate of less than 0.3mg / cm². 2 h) -1Although methyltriethoxysilane and dimethyldiethoxysilane contain methyl hydrophobic functional groups, giving the coating a low surface energy, these methyl hydrophobic functional groups are easily corroded by strong acids, thus increasing the surface energy and exhibiting hydrophilicity. After corrosion, silica alters the micro / nano structure of the coating surface, playing a crucial role in the contact angle; higher silica content results in a larger contact angle and better hydrophobic properties.
[0046] Example 2
[0047] A method for preparing a corrosion-resistant and anti-adhesion coating is basically the same as in Example 1, except that 270g of anhydrous ethanol, 30g of purified water, and 12g of ammonia are placed in a three-necked flask and stirred at 60°C for 30 minutes. Then, 30g of tetraethyl silicate is added dropwise, and stirring continues for 2 hours to obtain a mixed emulsion. 15g of silica micropowder is added to the mixed emulsion, and stirring is carried out for 1 hour. Then, 6g of hexadecyltrimethoxysilane is added dropwise, and stirring continues for 3 hours. After centrifugation for 30 minutes, the mixture is washed with anhydrous ethanol and dried in a drying oven at 70°C for 12 hours to obtain hydrophobic modified micro / nano silica particles. The prepared coating is sprayed onto a substrate and allowed to air dry naturally at 25°C for 48 hours. The coating thickness is 80 micrometers. A corrosion-resistant, anti-adhesion, and uniform coating suitable for preventing adhesion and blockage in coal powder silos is thus prepared.
[0048] Example 3
[0049] A method for preparing a corrosion-resistant and anti-adhesion coating is basically the same as in Example 1, except that 12g of methyltriethoxysilane and 6g of dimethyldiethoxysilane are ultrasonically dispersed in a mixed solution of 120g of isopropanol and water, wherein the ratio of isopropanol to water is 5:2. The pH of the solution is adjusted to 4 using acetic acid, and 10g of polytetrafluoroethylene powder is added. The mixture is stirred and reacted at 80°C for 6 hours. Then, 10g of hydrophobically modified micro / nano silica particles and 6g of micron-sized silicon carbide particles are added to the sample, and the system is stirred and reacted at 60°C for 5 hours to prepare the corrosion-resistant and anti-adhesion coating. The prepared coating is sprayed onto a substrate and allowed to air dry naturally at 25°C for 48 hours. The coating thickness is 100 microns. This results in a uniform, corrosion-resistant, and anti-adhesion coating suitable for preventing adhesion and blockage in coal powder silos.
[0050] Example 4
[0051] A method for preparing a corrosion-resistant and anti-adhesive coating is basically the same as in Example 1, except that 12g of methyltriethoxysilane and 6g of dimethyldiethoxysilane are ultrasonically dispersed in a mixed solution of 120g isopropanol and water, wherein the ratio of isopropanol to water in the mixed solution is M(isopropanol):M(water) = 5:2. Acetic acid is used to adjust the pH of the solution system to 5.
[0052] The prepared coating is sprayed onto the substrate and allowed to air dry naturally at 25°C for 48 hours. The coating thickness is 80 micrometers. This results in a corrosion-resistant, anti-adhesion, and uniform coating suitable for preventing sticking and clogging in pulverized coal feeding silos.
[0053] In summary, this invention provides a corrosion-resistant and anti-adhesion coating and its preparation method, as well as its application in pulverized coal feeding silos. It belongs to the field of special functional coating technology, primarily addressing the problems of pulverized coal adhesion and blockage in pulverized coal feeding silos. The coating preparation method uses methyltriethoxysilane and dimethyldiethoxysilane as the main organic solvents, and polytetrafluoroethylene powder, hydrophobically modified micro / nano silica particles, and micron-sized silicon carbide particles as functional fillers. These are uniformly mixed to form a coating system, thereby preparing a corrosion-resistant and anti-adhesion coating. The prepared corrosion-resistant and anti-adhesion coating has a contact angle of over 140°, excellent acid corrosion resistance, and effectively prevents pulverized coal adhesion, blockage, and clogging in pulverized coal feeding silos, improving the stability and safety of coal conveying systems.
[0054] Those skilled in the art should understand that variations can be implemented by combining existing technology with the above embodiments, which will not be elaborated here. Such variations do not affect the essence of the present invention, and will not be elaborated here either.
[0055] The preferred embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and the devices and structures not described in detail should be understood as being implemented in a conventional manner in the art. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the scope of the present invention. This does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the present invention's technical solutions still fall within the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant and anti-adhesive coating, characterized in that: Includes the following steps: 12 parts by weight of methyltriethoxysilane and 6 parts by weight of dimethyldiethoxysilane were ultrasonically dispersed in a mixed solution of 120 parts by weight of isopropanol and water. The pH of the solution was adjusted to pH=4.5 with acetic acid. 10 parts by weight of polytetrafluoroethylene powder were added, and the mixture was stirred and reacted completely at 70-80°C. Then, 10-14 parts by weight of hydrophobically modified micro / nano silica particles and 3-6 parts by weight of micron-sized silicon carbide particles were added, and the mixture was stirred and reacted completely at 50-60°C to prepare a corrosion-resistant and anti-adhesion coating. The hydrophobically modified micro / nano silica... The preparation method of the particles is as follows: 90 parts by mass of anhydrous ethanol, 10 parts by mass of purified water and 4 parts by mass of ammonia water are placed in a three-necked flask and stirred evenly at 50~60℃. Then, 10 parts by mass of tetraethyl silicate are added dropwise and stirred continuously to obtain a uniform mixed emulsion. 2~5 parts by mass of silica micro powder are added to the mixed emulsion and stirred evenly. Then, 2 parts by mass of hexadecyltrimethoxysilane are added dropwise and stirred until the reaction is complete. After centrifugation and washing with anhydrous ethanol, the mixture is placed in a drying oven and dried completely to obtain hydrophobic modified micro / nano silica particles.
2. The method for preparing a corrosion-resistant and anti-adhesion coating according to claim 1, characterized in that, The mass ratio of isopropanol to water in the isopropanol and water mixture is 5:
2.
3. A corrosion-resistant and anti-adhesive coating, characterized in that, The corrosion-resistant and anti-adhesion coating is prepared by the preparation method described in claim 1 or 2.
4. A corrosion-resistant and anti-adhesive coating, characterized in that, The corrosion-resistant and anti-adhesion coating prepared by the preparation method described in claim 1 or 2 is sprayed onto the substrate and allowed to air dry naturally.
5. The corrosion-resistant and anti-adhesion coating according to claim 4, characterized in that, The coating has a thickness of 60-100 micrometers, a water contact angle of over 140°, and a bonding strength with the substrate of over 28 MPa.
6. The application of the corrosion-resistant and anti-adhesion coating as described in claim 3 on the wall panel of the pulverized coal feeding silo.
7. The application of the corrosion-resistant and anti-adhesion coating as described in claim 4 or 5 on the wall panel of the pulverized coal feeding silo.
Citation Information
Patent Citations
Solvent-free pipeline inner wall anticorrosive hydrophobic coating and preparation method thereof
CN110845937A
Self-cleaning passive radiation refrigeration paint as well as preparation method and coating structure thereof
CN113278331A
